Bone mineral density and lean mass asymmetries are greater in cyclists than non-cyclists - Pimentel, R. E.; Baker, B. S.; Soliday, K.; Reiser II, R. F. (Journal of Sports Sciences, 2019)
Cyclists may be at greater risk of developing asymmetrical force and motion patterns than other ground-based athletes. However, functional asymmetries during cycling tend to be highly variable, making them difficult to assess. Dual-energy x-ray absorptiometry (DXA) measurements of areal bone mineral density (aBMD) and lean mass (LM) in the lower limbs may be a more sensitive and consistent method to identify asymmetries in cyclists. The goal of this study was to determine if competitive cyclists have greater levels of asymmetries in the lower body compared to non-cyclists using DXA. A secondary aim was to determine if aBMD and LM asymmetries change over the road cycling season. 17 competitive cyclists and 21 non-cyclist, healthy controls underwent DXA scans. Lower-body asymmetries were greater in cyclists compared to non-cyclists in aBMD and LM for all lower limb segments. However, these asymmetries did not tend to consistently favour a particular side, except for the pelvis having more LM on the dominant side. The were no longitudinal changes in aBMD or LM in the cyclists. Asymmetry analysis via DXA provides evidence that although functional asymmetries during cycling are variable, cyclists have increased lower body LM and aBMD asymmetries compared to non-cyclists.